Template-Free and Surfactant-Free Synthesis of Selective Multi-Oxide-Coated Ag Nanowires Enabling Tunable Surface Plasmon Resonance - Chi-Hang Tsai; Shih-Yun Chen; Alexandre Gloter; Jenn-Ming Song (Nanomaterials, 2020)
Without using templates, seeds and surfactants, this study successfully prepared multi-oxide-layer coated Ag nanowires that enable tunable surface plasmon resonance without size or shape changes. A spontaneously grown ultra-thin titania layer onto the Ag nanowire surface causes a shift in surface plasmon resonance towards low energy (high wavelength) and also acts as a preferential site for the subsequent deposition of various oxides, e.g., TiO2 and CeO2. The difference in refractive indices results in further plasmonic resonance shifts. This verifies that the surface plasma resonance wavelength of one-dimensional nanostructures can be adjusted using refractive indices and shell oxide thickness design.